KEBIJAKAN STABILISASI HARGA BERAS - Ranni Resnia; Astari Wirastuti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
The rice retail price the research period is relatively stable and in a moderat range. The most unstable rice retail prince happened in Jakarta and Surabaya. The third and fourth week of December and the second week until the end of February are the periods which need special attention from the Government of Indonesia (GOI). According to the research results, there are five variables that influence the price of rice which are: previous rice prince, gasoline price, harvested area, final stock of rice by Bulog, and market operation by Bulog. Rice price is more unstable if the fluctuation of gasoline priceis higher than previous price, the rice stock mobilization from Bulog worst, rice import volume is low, and the market operation policy is more effective if it is supported by the stable gsoline price because this price in stability has the strongest influence towards rice price instability. To minimize the impact of the increasing rice price to the poor, GOI is in the right track by implementing the Safety Net Programme ( Jaringan Pengaman Sosial/JPS programme). Nevertheless, this programme needs further improvement.There are few alternative to improve PP No. 68/2002. Firstly, if the price increases more than 25% to be the indicator for price unstabil then the time reference should be changed from 3 months i9nto 6 months. Secondly, if we want to the price indicator decrease from 25% to 15% if we still want to use the 3 months time reference.